OCULAR CYSTICERCOSIS: A CASE REPORT - KASHYAP, ADITYA; NEGI, SHALOO; SHARMA, SMRITI (International Journal of Current Pharmaceutical Research, 2024)
Ocular cysticercosis, though rare, can be extraocular or intraocular. Ocular manifestations usually occur as a part of a systemic infection and can lead to partial or complete visual impairment over a 3-5 y period. The parasite reaches the posterior segment of the eye via the high-flow choroidal circulation through the short ciliary arteries. A 35 y old female patient presented to us with history of blurring of vision in right eye over one week. Fundus examination revealed an oval translucent cyst of about 4 mm in diameter. The patient underwent USG B scan, which revealed well-circumscribed cystic lesion in posterior vitreous.